Analisis Potensi Wisata Desa Lubuk Dagang Kecamatan Sambas untuk Meningkatkan Kesejahteraan Masyarakat - Ervina, Ervina; Tampubolon, Budiman; Sugiarto, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractVillage this research aims to describes. To analyze the potential of lubuk dagang to be a tourism village. To analyze factors the influence of lubuk dagang's development. The vilaagers' perception of lubuk dagang village, sambas district to developed to be a tourism area to analyze how big the developing lubuk dagang village contribution becomes a tourism area to improve villagers' prosperity this research ia descriptive research with qualitative approach. The subjects of this research were village officials and public figure. Collecting data collected by observing, interviewieng and documentating data. The technique of alayzing data are reducting data, displaying data, and taking conclusion. The Tringgulasi used for explain the right of data which is using data resources. the result of this research shows that: (1) thr villagers' participation in build a tourism village plan. a) the survei, villagers gave information about situation and potential of the village b) the kind of potential tourism which is potentially to develop in lubuk dagang village are embatan belian, jungle tourism, and culter tourism; c) rhe factors influenzed depeloving village :(1) The intern factor, enthusiasm and desire from themselves. The villages goverment as villagers organizer to participate in meeting activities. (2) external factor the region government order as the fasilitator. And alsok obstacle factor the socialiszation process is not optimal yet, the business every villagers are differential, the lack of villagers' awareness to the tourism villagers development planning. and the half of villagers do not understand much about tourism village. d) The villagers' perseption to the village tourism development. Villagers gave some react to accesbility, infrastucture and etc. contributions or villagers perticipation are in mind and manpower and also in experts.Keywords : village potential, villagers' contribution